DETERMINANTS OF ORI001 TYPE GOVERNMENT BOND - Yosandi Yulius (Economic Journal of Emerging Markets, 2011)
The need to build a strong bond market is amenable, especially after the 1997 crises. This paper analyzes the influence of deposit interest rate, foreign exchange rates, and Composite Stock Price Index on yield-to-maturity of Bond Series Retail ORI001, employing monthly data from Bloomberg information service, 2006(8) to 2008(12), using Generalized Autoregressive Conditional Heteroscedasticity type models. It finds the evidence that deposit interest rate and exchange rate have positive significant influence on the bond, and that stock index has a negative significant influence on the bond. It also finds that Deposit Interest Rate, exchange rate, and the stock index significantly influence the bond altogether.Keywords: Interest rate, exchange rate, composite stock price index, yield-to-maturity, bondJEL classification numbers: G12, G15